2014
DOI: 10.3109/10428194.2013.858816
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb protein EZH2 expression in diffuse large B-cell lymphoma is associated with better prognosis in patients treated with rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone

Abstract: Polycomb group (PcG) proteins are evolutionarily conserved regulators of gene expression that contribute to normal lymphocyte development, and are involved in malignant transformation of these cells. Recently, BMI1 and EZH2 have been shown to be involved in lymphomagenesis and oncogenesis. We tried to elucidate the role of EZH2 as a prognostic factor for diffuse large B-cell lymphoma (DLBCL). High-level expression of EZH2 (EZH2 ≥ 70%) was associated with superior overall survival (OS) of 85.8% compared to low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…Following the thresholds defined by a previous study [ 25 ], low EZH2 IHC expression (< 70% of tumoral cells stained) was observed in 36% of patients (55% ABC and 39% GCB), whereas high EZH2 IHC expression (≥ 70% of tumoral cells stained) was observed in 64% of patients (41% ABC and 53% GCB). In univariate analysis, low EZH2 IHC expression was significantly associated with superior OS ( p = 0.035, OS = 77% at 3 years versus 35%) and PFS ( p = 0.02, PFS = 77% at 3 years versus 29%) in ABC patients treated with R-chemotherapy (Figure 4A, 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the thresholds defined by a previous study [ 25 ], low EZH2 IHC expression (< 70% of tumoral cells stained) was observed in 36% of patients (55% ABC and 39% GCB), whereas high EZH2 IHC expression (≥ 70% of tumoral cells stained) was observed in 64% of patients (41% ABC and 53% GCB). In univariate analysis, low EZH2 IHC expression was significantly associated with superior OS ( p = 0.035, OS = 77% at 3 years versus 35%) and PFS ( p = 0.02, PFS = 77% at 3 years versus 29%) in ABC patients treated with R-chemotherapy (Figure 4A, 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study in breast cancer also showed that low EZH2 expression is correlated with better Distant Disease Free Survival (DDFS) [ 12 ], corroborating our findings. On the contrary, Lee et al recently analyzed EZH2 IHC expression in a cohort of DLBCL patients of similar size and showed that high EZH2 expression was associated with superior OS, with EZH2-high ABC patients being the subgroup with the highest OS, although this finding was not quite statistically significant in multivariate analysis [ 25 ]. Compared to Lee et al, our cohort was marginally older, with a larger percentage of patients over 60 years old or with Ann Arbor stage III–IV at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…79,81 These inhibitor and demethylating agents might be a useful therapeutic option for patients with an EZH2 hypermethylation phenotype. 87,88 Other Epigenetic Gene Signatures…”
Section: Kruppel-like Factor 4 (Klf4)mentioning
confidence: 99%
“…EZH2 has been reported to be of both prognostic and therapeutic value in different tumors, such as small cell lung carcinoma [70], breast cancer [71, 72], cervical carcinomas [73], urinary tract carcinoma [74], and lymphoma [75]. Through gene expression profiling, EZH2 was found to be overexpressed in hormone-refractory metastatic prostate cancer [69].…”
Section: Molecular Markersmentioning
confidence: 99%